D-ROOM: HOTEL BOOKING AND BEDROOM RENTAL APPLICATION FOR LHOKSEUMAWE AND NORTH ACEH REGIONS BASED ON ANDROID MOBILE - Ian Wooton; Stephen Martin; Joko Saputra (Bulletin of Engineering Science, Technology and Industry, 2023)
The hotel booking application, developed on the Android platform, presents a comprehensive and user-centric solution for accessing an extensive array of room information in the city of Lhokseumawe and the North Aceh Regency. Through its well-designed interface and intuitive functionalities, the platform offers users a seamless experience in searching, comparing, and booking accommodations that meet their specific needs and preferences. One of the application's key strengths lies in its capacity to aggregate a diverse range of room listings from various providers, encompassing hotels, guesthouses, and rental properties, all conveniently accessible within a single platform. This centralization of information empowers users with a plethora of choices, facilitating an informed decision-making process when selecting their ideal lodging. To ensure the utmost authenticity and credibility of the room listings, the application implements a robust admin review process for all submitted advertisements. This meticulous evaluation guarantees that only verified and genuine offerings are published, fostering a sense of trust and reliability among users. Additionally, the platform's user-friendly interface enables effortless navigation through the available listings, providing essential details such as room features, amenities, images, and transparent pricing for specific periods. Users can easily compare options, making it easier to find accommodations that align with their budget and preferences. By streamlining the booking process and offering a wide array of options, the hotel booking application aims to revolutionize how users access and manage room data. It empowers both travelers and property owners in Lhokseumawe and the North Aceh Regency by providing a valuable and efficient tool to optimize the booking experience and enhance customer satisfaction. Through this comprehensive solution, the application sets the standard for modern and convenient accommodation search and booking, contributing to a seamless and enjoyable travel experience for all users.